The Effect of Moodle-Based Vocabulary Quiz on EFL Grade-10 Students’ Vocabulary Retention : - Nguyễn, Quốc Bảo (Trường đại học Cần Thơ, 2018)
The current experimental study was conducted with an aim of measuring the effect of Moodle-based vocabulary quiz on EFL grade-10 students’ vocabulary retention. Then, the results of the study were further analyzied to observe: 1) whether there was any statistically significant difference in vocabulary retention between blended learning with Moodle-based vocabulary quiz and traditional vocabulary learning with paper-based vocabulary practice, 2) what the effect size of Moodle-based vocabulary quiz was when vocabulary retention is considered, and 3) whether there was any statistically significant difference in vocabulary retention between male students and female students who received blended learning.